2016
DOI: 10.17520/biods.2015127
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of phytoplasmas: research status and prospects

Abstract: Phytoplasmas are cell wall-less prokaryotic pathogens causing many plant diseases with various host plants, widely geographical distribution and adverse impacts on economics and environments. Abundant genetic diversity of the phytoplasmas has been evidenced by vast researches. In the paper, we conducted a comparatively systematic and comprehensive schematic review and comment on the research status of phytoplasma genetic diversity. We discussed the potential research directions with respect to research technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The results showed that the established ddPCR method was reliable for quantitative detection of AYL phytoplasma, with relatively good effect. The tuf gene is a functional protein coding gene and a relatively conserved sequence in the phytoplasma which plays an important role in protein translation and evolution of phytoplasma (Koui et al, 2003; Lai et al, 2014; Lee et al, 2000; Schneider et al, 1997; Yu et al, 2016,b, 2017, 2018). In the study, the tuf gene was used as a diagnostic assay for AYL phytoplasma for the first time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the established ddPCR method was reliable for quantitative detection of AYL phytoplasma, with relatively good effect. The tuf gene is a functional protein coding gene and a relatively conserved sequence in the phytoplasma which plays an important role in protein translation and evolution of phytoplasma (Koui et al, 2003; Lai et al, 2014; Lee et al, 2000; Schneider et al, 1997; Yu et al, 2016,b, 2017, 2018). In the study, the tuf gene was used as a diagnostic assay for AYL phytoplasma for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a ddPCR detection system for AYL phytoplasma belonging to 16SrI group, and associated with AYL disease in Hainan Province of China, was developed based on the tuf gene sequence. The tuf gene is a conserved gene in phytoplasmas and has been widely used in the detection, identification and study of genetic variation of phytoplasmas (Koui, Natsuaki, & Okuda, 2003; Lee, Davis, & Gundersen‐Rindal, 2000; Schneider, Gibb, & Seemüller, 1997; Wang et al, 2010; Wang et al, 2017; Yu et al, 2016,b, 2017, 2018). Early detection of the AYL phytoplasma using developed ddPCR system can assist in managing the disease by cutting the transmission route of AYL phytoplasma from the source, effectively preventing the spread and epidemic of phytoplasma and its related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, jujube witches'-broom, mulberry dwarf, paulownia witches' -broom, wheat blue dwarf are widely distributed and have caused serious damaged in China. SCWL disease, rice orange leaf disease, cherry lethal yellow, groundnut witches' broom, and areca nut yellow leaf disease, are distributed in some areas in China (Zhang et al, 1995;Mou et al, 2011;Yu et al, 2016;Song et al, 2018) (Table 1).…”
Section: Historical Backgroundmentioning
confidence: 99%